Effect of Pericardium Point Acupressure 6 on Gravidarum Emesis Trimester I Pregnant Women at the Working Area Public Halth Center Koto Berapak In 2020 - Nadiah Fadhilah; Mayetti Mayetti; Rosfita Rasyid (Institute of Computer Science (IOCS), 2021)
Every pregnant woman experiences different degrees of nausea. Efforts to overcome it through pharmacological and non-pharmacological therapies. Non-pharmacological therapies such as herbs, acupuncture and acupressure. In pregnant women, the tendency to use non-pharmacological therapy has increased. The purpose of this study was to determine the effect of Acupressure Point Pericardium 6 on Emesis Gravidarum in 1st trimester pregnant women. This research is an experimental study using a pre and post control group design approach. The research was conducted in July - November 2020 in the work area of ​​the Koto Berapak Health Center, Pesisir Selatan Regency. The sample in this study were 26 primigravida pregnant women who experienced emesis gravidarum in the first trimester and met the inclusion and exclusion criteria as many as 26 people who were selected by simple random sampling. The sample was divided into two groups using odd even numbers, where each 13 samples were in the experimental and control groups. Data were analyzed using Mann Whitney. The results showed that the mean score of emesis gravidarum before acupressure in the experimental group was 8.69 ± 0.48 and the control group was 7.62 ± 1.19. The mean score of emesis gravidarum after acupressure in the experimental group was 3.31 ± 0.48 and the control group was 5.69 ± 1.75. The mean reduction in the emesis gravidarum score of the experimental group was 5.38 ± 0.50 and the control group was 1.92 ± 1.80. There was a significant difference in emesis gravidarum scores between the experimental and control groups (p < 0.05). The conclusion of this study is that there is an effect of acupressure point pericardium 6 in the form of a significant reduction in the frequency of nausea and vomiting in first trimester pregnant women who experience emesis gravidarum.